Neuroendocrine tumor cells in prostate cancer: Evaluation of the neurosecretory products serotonin, bombesin, and gastrin$dimpact on angiogenesis and clinical follow-up - Heinrich, Elmar; Trojan, Lutz; Friedrich, Dorothee; Voß, Martin; Weiß, Christel; Michel, Maurice Stephan; Grobholz, Rainer (The prostate, 2011)
BACKGROUND Neuroendocrine differentiated tumor cells (NETC) can be found in a large portion of prostate carcinoma (PCa) specimens. This is the first study to systematically quantify and analyze the influence of the NETC distribution and of their secretory products, serotonin, bombesin, and gastrin, on angiogenesis and in the clinical follow-up of PCa patients. METHODS 175 PCa specimens were included in this study. NETC were displayed using the marker CgA. Specimens showing a high expression of CgA were analyzed for serotonin, bombesin, and gastrin. Blood vessels were stained with the epitope CD34. Data was analyzed for inter-correlation and its correlation to clinical-pathological parameters and the results of a mid-term follow-up. RESULTS The number of NETC was correlated with the pT-status and the Gleason score. Specimens with high NETC expression had an increased microvessel density (MVD). No correlation between the neurosecretory products and the clinical-pathological parameters was found. High NETC expression, high bombesin expression and increased MVD were associated with early treatment failure in the follow-up. CONCLUSION NETC have an influence on angiogenesis and are correlated with the clinical-pathological parameters. A high expression of NETC is associated with an early failure of treatment. Our study underlines the importance of NETC in prostate cancer. Prostate 71:1752-1758, 2011. © 2011 Wiley Periodicals, Inc.
First published: 07 April 2011
Gesehen am 04.10.2022